BUDAYA SEKOLAH DAN PERANNYA DALAM PENDIDIKAN - Elisabet Tantiana Ngura; Maria Euvania Masi; Silviana Vernand Suda; Marsiana Beku (STKIP Subang, 2026)
This study aims to analyze the role of school culture in forming a holistic educational environment in Kober St Leonard Warikeo. Qualitative methods were used through observation and interviews during PLP 1 (17–27 February 2025) with a focus on school culture, learning processes, and interactions between school members. Participants included 13 students, teachers, and education personnel. The results of the study indicate that the school culture in the institution is supported by a clear vision and mission, structured rules, and co-curricular and extracurricular activities that support student development. As many as 76.93% of students are in the “very well developed” category, supported by positive practices such as the 3S culture (smile, greet, say hello), high discipline, and teacher role models. Teachers demonstrate a commitment to active, innovative learning, and responsive mentoring. Other supporting factors include a beautiful school environment, adequate facilities, and positive responses to stakeholder input. These findings confirm that a collaborative, value-oriented, and adaptive school culture contributes significantly to the achievement of student development academically and in character. The implication is that schools need to strengthen participatory culture and consistency in implementing rules to ensure the sustainability of educational quality. This study recommends the integration of school culture as a primary strategy in developing a holistic curriculum at the PAUD level.